Local Wisdom Based-Child Poetry Compilation Book As A Complementary Learning In Primary School - Kironoratri, Lintang (Universitas Negeri Makassar, 2020)
This research aims to develop local wisdom based child poetry compilation books as complementary learning of Indonesian language lessons at primary schools. The applied method was research and development with these following stages: (1) finding out the potentials and problems, (2) collecting the data, (3) designing the product, (4) validating the design, (5) revising the design, (6) trying out the product, and (7) revising the product. The applied instruments were (1) the data of local wisdom based child poetry compilation book necessity for a higher level of primary schools, (2) the validation result data of the book prototype judged by the experts, and (3) the result of the product trial run. The planning stage of this child's poetry book was applied to support the Indonesian language course learning in primary schools. It consists of concepts and the child poetry book design. By referring the obtained data, based on the necessity questionnaire, 90% of the teachers stated that they needed the child’s poetry book. Meanwhile, the experts’ validation results deemed this book valid. In the trial run of the product, the last stage of this research showed that 85% of the teachers stated this child's poetry book had met the learning material necessity.